Freshwater ostracods (Crustacea) and environmental variability of polygon ponds in the tundra of the Indigirka Lowland, north-east Siberia - Schneider, Andrea; Wetterich, Sebastian; Schirrmeister, Lutz (Dr.); Herzschuh, Ulrike (Prof. Dr.); Meyer, Hanno; Pestryakova, Luidmila A. (Prof. Dr.) (Polar Research, 2016)
Freshwater ostracods (Crustacea, Ostracoda) are valuable biological indicators. In Arctic environments, their habitat conditions are barely known and the abundance and diversity of ostracods is documented only in scattered records with incomplete ecological characterization. To determine the taxonomic range of ostracod assemblages and their habitat conditions in polygon ponds in the Indigirka Lowland, north-east Siberia, we collected more than 100 living ostracod individuals per site with a plankton net (mesh size 65 mm) and an exhaustor system from 27 water bodies and studied them in the context of substrate and hydrochemical data. During the summer of 2011, a single pond site and its ostracod population was selected for special study. This first record of the ostracod fauna in the Indigirka Lowland comprises eight species and three additional taxa. Fabaeformiscandona krochini and F. groenlandica were documented for the first time in continental Siberia. Repeated sampling of a low-centre polygon pond yielded insights into the population dynamics of F. pedata. We identified air temperature and precipitation as the main external drivers of water temperatures, water levels, ion concentrations and water stable isotope composition on diurnal and seasonal scales.